Moulding the Icelandic Tax System. Primary-Industry-Based Special Interest Groups, Taxation, Tax Expenditure, Direct and Indirect State Support, and the Shaping of Tax Rules - Jóhannes Hraunfjörð Karlsson 1959- (2014)
This paper outlines the main developmental aspects of the taxation system (the definition of tax-base, tax rate, and the tax structure) and its administration according to primary-industry-based special interest groups in Iceland, from the time financial independence was obtained in 1874 to the present, the chief characteristics of Icelandic tax policy, and its contribution to developing the economic base. Special consideration is given to how corruption related to the tax system affects tax evasion, tax avoidance and inequality. Evading taxes is illegal, and that introduces a fundamental difficulty into the measurement of tax evasion. The term “Non-Observed Economy” (NOE) refers to all economic activities for which unreported payments are made. Unreported payments can leave a trace: The three different methods to measure the gross domestic product, GDP, (the production approach; the expenditure approach; and the income approach) can be used as a tool to measure the NOE. The outcome of all these three methods should be the same. However, we can’t distinguish between tax evasion and other undeclared activities. Corruption is principally a governance issue. A weak administration and pervasive corruption are related, and extractive institutions thrive on this. We point out how Icelandic institutions’ failure to manage society by means of social, judicial, political and economic balances lies in the taxation system. There is no link between taxation policies or tax rates with Iceland’s economic growth, as taxes were fixed in response to the economic situation rather than according to proactive government planning. In the 1940s, the rate of tax evasion is estimated to have been between 35 and 45 percent, but in the events leading up to the crisis 2008, between 15 and 25 percent of the tax revenue. The Icelandic tax system is such that the taxes are highly regressive and proportionally decreasing as the income is higher. Other causes of inequality are low replacement incomes and transfer payments between income groups ...